Cerebral Embolic Protection Devices: Current State of the Art - Ankit Agrawal; Toshiaki Isogai; Shashank Shekhar; Samir Kapadia (US Cardiology Review)
Transcatheter aortic valve replacement (TAVR) has become a first-line treatment for severe aortic stenosis with intermediate to high-risk population with its use increasingly expanding into younger and low-risk cohorts as well. Cerebrovascular events are one of the most serious consequential complications of TAVR, which increase morbidity and mortality. The most probable origin of such neurological events is embolic in nature and the majority occur in the acute phase after TAVR when embolic events are most frequent. Cerebral embolic protection devices have been designed to capture or deflect these emboli, reducing the risk of peri-procedural ischaemic events. They also carry the potential to diminish the burden of new silent ischemic lesions during TAVR. Our review explores different types of these device systems, their rationale, and the established clinical data.